Irrigation management of a peach orchard - Nagy, A.; Riczu, P.; Tamás, J.; Szabó, Z.; Nyéki, J.; Soltész, M. (International Journal of Horticultural Science, 2012)
The research field was at Siófok, in Hungary, which is situated in the South East side of Lake Balaton. The physical characteristic of the soil is sandy loam and loam and the peach orchard is irrigated. Mainly Sweet Lady (early ripening), Red Heaven (medium ripening) and Weinberger (early ripening) species were installed. In order to achieve the optimal developement level of trees and maximal yield amount and fruit diameter (Sweet Lady 60–75 mm, Red Heaven 60–70 mm, Veinberger 50–60 mm) continous water and nutrient supply is required. The irrigation modeling was set by CROPWAT 8.0 based on the climatic, crop and soil data inputs of the last 10 years. Based on the results, large amount of water is needed for optimal growth of fruit trees, particularly in the summer months, in case of active ground cover (+) and bare soil (–) as well. The irrigation requirement of a tree was found maximum 4 l/hour in certain cases. This irrigation intensity can be achieved – calculated with 12-hour operating time – by using continuous water NAAN Tif drip tube with 2 l/h flux on 3 atm pressure with 16 mm pipe diameter. If lower irrigation intensity is required irrigation can be controlled by the decreased the operation time.